2006
DOI: 10.1186/1475-925x-5-62
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of human uterine cervical electrical impedance measurements derived using two tetrapolar probes of different sizes

Abstract: Background: We sought to compare uterine cervical electrical impedance spectroscopy measurements employing two probes of different sizes, and to employ a finite element model to predict and compare the fraction of electrical current derived from subepithelial stromal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Both magnitude and phase at high frequencies were relatively smaller and more tightly grouped. This has also been observed by other researchers and can be explained by greater ease of penetrating cell walls with high frequency signals [1921]. Lower frequency signals have greater difficulty penetrating cell walls and injected current tends to follow extracellular paths.…”
Section: Pilot Datasupporting
confidence: 76%
“…Both magnitude and phase at high frequencies were relatively smaller and more tightly grouped. This has also been observed by other researchers and can be explained by greater ease of penetrating cell walls with high frequency signals [1921]. Lower frequency signals have greater difficulty penetrating cell walls and injected current tends to follow extracellular paths.…”
Section: Pilot Datasupporting
confidence: 76%
“…Impedance can be measured by placing electrodes on the cervix. A study of electrical impedance in 50 nonpregnant and 90 pregnant women found impedance to be decreased in the first trimester cervix as compared to the nonpregnant cervix, but, surprisingly, impedance in late pregnancy were larger than in early pregnancy or the nonpregnant state 42 The authors speculated that perhaps this was due to increased cellular and collagen content in late pregnancy. A subsequent study impedance for prediction of successful labor induction in 200 women presenting for induction at term found that the measurements were only weakly correlated.…”
Section: Quantifying Cervical Remodelingmentioning
confidence: 98%
“…It has been showed that the electrode probe used to measure the impedance of tissue plays an important role for getting accurate readings and hence the measurements can be improved by changing the probe geometry (Jones et al, 2003;Gandhi et al, 2006;Bertemes Filho et al, 2003). Researches performed by Gonzalez-Correa et al (Gonzalez-Correa et al, 2005) showed that the resistivity of various tissues increase as the pressure of the measurement probe is increased.…”
Section: Introductionmentioning
confidence: 99%